Work-Life Balance, Organizational Support, And Job Burnout As Determinants of Turnover Intention In Generation Z - Sukandar Nur, Haris; Darmi Astuti, Sih; Ikasari, Hertiana (International Journal of Science, Technology & Management, 2025)
This study aims to analyze the influence of work-life balance and organizational support on job burnout and its implications for turnover intention among Generation Z educational staff at Esa Unggul University. This study used a quantitative approach with a survey method of 115 Generation Z respondents. The research instrument was a structured questionnaire that had been tested for validity and reliability. The collected data were analyzed using Structural Equation Modeling (SEM-PLS) using SmartPLS 4 software, which allows for simultaneous testing of causal relationships between variables. The results showed that work-life balance had a significant negative effect on job burnout and turnover intention. This means that the higher the level of work-life balance perceived by employees, the lower the risk of burnout and intention to leave. Furthermore, organizational support has been shown to play a significant role in reducing job burnout levels and reducing the likelihood of resignation. Conversely, job burnout has a significant positive effect on turnover intention, indicating that the higher the level of job exhaustion experienced, the greater the likelihood that employees will plan to leave the organization. Theoretically, this study expands the literature on Generation Z dynamics in the workplace, emphasizing the role of work-life balance and organizational support in influencing turnover intention. Furthermore, the results corroborate previous research findings that confirm a strong relationship between burnout and turnover intention. Practically, this study provides strategic recommendations for university management to strengthen employee wellness policies, develop work flexibility, provide career development programs, and build a supportive organizational culture.